The Role of Non-Marketable Assets to Determine the Cost of Capital: Evidence from India - Das, Sudipta; Barai, Parama (Asian Journal of Business and Accounting, 2017)
Manuscript type: Research paper. Research aims: This paper aims to examine the role of nonmarketable assets namely, stock index, government bond index, human capital and real estate in a multi-asset proxy for the true market portfolio. It also examines the sensitivity of risk-return tradeoffs with different market portfolio compositions for both the conditional and unconditional versions of the asset pricing model. Design/ Methodology/ Approach: This paper extends on Mayers’ (1972) model by building a composite market portfolio which consists of stock, bond, human capital and real estate. The crosssection of asset returns is tested with Fama and Macbeth’s (1973) regression method. The capital asset pricing model (CAPM) uses the Kalman filter based approach to estimate the conditional factor loadings. Research findings: This study finds that when per unit of risk premium is equal, the market model standard beta over-estimates the systematic risk that is measured by the composite market portfolio. The effect of bond, human capital and real estate on the complete market portfolio does not have much impact on the empirical testing of the CAPM. However, the conditional model shows a significant and positive risk premium. Theoretical contributions/ Originality: Despite the importance of the non-marketable assets, many studies have rarely integrated or validated these in an asset-pricing framework, within an emerging market. Thus, the present study seeks to advance the theoretical and empirical understanding of the role of non-marketable assets in the composition of market proxies for an asset pricing model, in India. Practitioner/ Policy implications: The validity of the CAPM is insensitive to the inclusion of non-marketable assets in the market portfolio. This implies that investors use prior belief and conditioning variables as predictive variables to determine the cost of capital. The outcome of this study provides academics and practitioners a better understanding of the cross-sectional behaviour of stock returns in the Indian market. Research limitation: The limited work done on the Indian capital market coupled by the limited availability of non-marketable data in this study, may constrain the comparison of the results. In addition, the outcome drawn from this study cannot be generalised on other emerging markets as the focus of this study was only on the Indian capital market. Keywords: Fama-MacBeth Regression, Kalman Filter, Mayers CAPM, Non-marketable Assets. JEL Classification: G12, G31